2015
DOI: 10.3989/mc.2015.05915
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the microstructure and technological properties of porcelain stoneware. A review

Abstract: Porcelain stoneware is a strongly sintered ceramic material fabricated from ball clays-quartzfeldspar mixtures. Porcelain stoneware is characterized by its excellent technical and functional properties (low water absorption, high mechanical properties, resistant to chemical substances and cleaning agents, aesthetic possibilities …). These characteristic and technical features make that among the different types of ceramic tile, porcelain stoneware is the ceramic product that in the last years has best withstoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 46 publications
2
32
0
2
Order By: Relevance
“…The coarse closed porosity increases as the amount of PG in the initial composition increases ( Fig. 6c; d), which is likely to be responsible for the reduction observed in bending strength, given that these pores can act as stress concentrators and facilitate fracture [44]. Fig.…”
Section: Materials Characterisationmentioning
confidence: 93%
“…The coarse closed porosity increases as the amount of PG in the initial composition increases ( Fig. 6c; d), which is likely to be responsible for the reduction observed in bending strength, given that these pores can act as stress concentrators and facilitate fracture [44]. Fig.…”
Section: Materials Characterisationmentioning
confidence: 93%
“…In the liquid phase sintering, progressive closure of the capillaries forming open porosity is occurring, and an increment of closed porosity with a smaller pore size begins [9]. The low density and densification percentage at this temperature can be explained by the presence of a greater amount of vitreous phase with a lower density than crystalline phases.…”
Section: Shaped Ceramicmentioning
confidence: 99%
“…There are studies on pressing and extruding methods and their effect on flexural strength, where higher values were found for pressing [8]. Microstructure and porosity have been analyzed for each forming method, and a suitable classification with respect to water absorption has been defined for several applications [9]. A comparative study on the effect of dry pressing, slip casting and extruding found higher densification when extruding, while intermediate processing performance was observed for dry pressing [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, tiles with 6-10% water absorption are classified as group BIII, and SQ4 with 7.1% is within this range. These are not suitable for use as floor tiles [22].…”
Section: Water Absorptionmentioning
confidence: 99%